'It's bit of an eye opener' – A qualitative study of women's attitudes towards tanning, sun protection and a facial morphing intervention. Issue 3 (4th March 2018) - Persson, Sofia; Grogan, Sarah; Dhingra, Katie; Benn, Yael
Abstract : Objective : Skin cancer is to a large degree behaviourally preventable, meaning that evidence-based interventions have scope to make a difference. Previous research indicates that appearance-based interventions such as facial morphing may be more effective than health-based interventions, and that it can personalise the issue of skin cancer. Method : This study examined attitudes to UV exposure, as well as reactions to a facial morphing intervention, through interviews with 25 women aged 35 years and older. Results : Thematic analysis revealed four themes; two regarding attitudes to UV exposure (confusion and contradiction, and change and continuity), and two relating to the facial morphing intervention (negative reactions to UV-exposed photo and positive outcomes of the intervention). Women experienced a number of barriers to adopting safer behaviour in the sun; their current attitudes to UV exposure had been shaped by available information sources throughout their ageing. They expressed negative evaluations of the UV photo, which fed directly into motivation to reduce UV exposure. Conclusions : These results can be interpreted along the lines of goal-directed behaviour. This type of intervention has the potential to reduce UV exposure among this participant group, something that needs to be further investigated with randomised control trials.